The Role of Legal Philosophy in Building a Fair and Just Legal System (Examining the Legal System in Lawrence M. Fiedman's theory) - Yosep Copertino Apaut; Egiony Saunoah (Jurnal Restorasi : Hukum dan Politik, 2025)
This paper examines the role of legal philosophy in building a just and fair legal system in Indonesia. Legal philosophy, as a critical reflection on the nature, purpose, and fundamental values of law, provides normative and ethical foundations for the formulation and enforcement of legal norms. The main issue addressed is the weakness of law enforcement in Indonesia, which is often influenced by corruption, political intervention, and the lack of integrity among law enforcement officers, thereby deviating from the ideals of justice. The study employs a normative research method through literature review, analyzing classical to modern philosophical thoughts as well as Lawrence M. Friedman’s legal system theory, which consists of structure, substance, and legal culture. The findings show that the effectiveness of the legal system is not solely determined by statutory regulations but also depends on the integrity of legal institutions and the prevailing legal culture in society. Therefore, legal philosophy plays a crucial role as a reflective instrument to ensure that law achieves its fundamental goals of justice, legal certainty, and utility in a balanced manner.